A Logic-Tree Approach for Probabilistic Seismic Hazard Assessment in the Administrative Region of Attica (Greece) - George Kaviris; Angelos Zymvragakis; Pavlos Bonatis; Vasilis Kapetanidis; Ioannis Spingos; Spyridon Mavroulis; Evelina Kotsi; Efthymios Lekkas; Nicholas Voulgaris (Applied Sciences, 2023)
Probabilistic Seismic Hazard Assessment (PSHA) was carried out for the administrative region of Attica (Greece). Peak Ground Acceleration (PGA) and Peak Ground Velocity (PGV) values were calculated for return periods of 475 and 950 years for five sub-areas covering the entire region. PGA hazard curves and Uniform Hazard Spectra (UHS) in terms of spectral acceleration (Sa) values were generated for Athens, Methana, and the capitals of each island of Attica (Salamina, Aegina, Poros, Hydra, Spetses, Kythira, and Antikythira). Area sources were adopted from the Euro-Mediterranean Seismic Hazard Model 2013 (ESHM13) and its update, ESHM20, taking into account both crustal and slab tectonic environments. Ground Motion Prediction Equations (GMPEs) proposed for the Greek territory were ranked for PGA and PGV. Each GMPE was reconstructed as a weighted model, accounting for normal and non-normal focal mechanisms for each area source. PGA, PGV, and Sa values were computed using a logic tree, integrating the seismotectonic models as major branches and sub-logic trees, comprised of multiple ranked GMPEs for each area source, as minor branches. The results showed higher seismic hazard values in sub-areas near the Gulf of Corinth and the slab interface, which could indicate a need to revise the active building code in Attica.